Laser assisted modified lip repositioning surgery for the treatment of excessive gingival display using Y V plasty: A case report - Simran Ghumman; Devinder Singh Kalsi; Vikrant Sharma; Khushboo Arora; Ajit Jaiswal; Girish Chaudhary (Wolters Kluwer Medknow Publications, 2023)
Excessive gingival display is matter of concern for a lot of patients and affects their psychological well-being. Various methods have been employed to reduce excessive gingival display but with variable results. Modified Lip repositioning is a surgical way to correct gummy smile by limiting the retraction of the elevator smile muscles and yet preserve the labial frenum using Y-V plasty using a method that gives long term results along with being non-invasive and has high patient compliance. After thorough disinfection and achieving adequate anaesthesia, the strip of mucosa which had to ablated was marked with a laser, which was twice the amount of gingival display seen in the patient. After carrying out laser ablation of the marked tissue, and performing Y-V plasty, the surgical area was evaluated and the wound margins were approximated with multiple interrupted sutures. The patient was put on a regular follow-up. The results revealed a marked reduction in gingival display at the 3-month follow-up. Overall gingival display reduced from 6 mm to 2 mm.